Life Expectancy as a Quality of Life Indicator - Gulshara Aimbetova; Gulzhan Dossybayeva; Roza Suleimenova; Aliya Turgambayeva; Assiya Turgambayeva (Tehran University of Medical Sciences, 2022)
No Abstract